2019
DOI: 10.2147/dddt.s220190
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bone marrow mesenchymal stem cell-derived exosomes attenuate D-GaIN/LPS-induced hepatocyte apoptosis by activating autophagy in vitro</p>

Abstract: Background Acute liver failure is an inflammation-mediated hepatocyte injury. Mesenchymal stem cell (MSC) transplantation is currently considered to be an effective treatment strategy for acute liver failure. Exosomes are an important paracrine factor that can be used as a direct therapeutic agent. However, the use of bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) in the treatment of acute liver failure has not been reported. Purpose Here, we established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 46 publications
(38 reference statements)
1
52
0
1
Order By: Relevance
“…There were reports that exosomes could attenuate diabetic nephropathy and D-GaIN/LPS-induced hepatocyte injury by promoting autophagic ux and inhibiting apoptosis [31,32]. Therefore, we also examined whether exosomes could inhibit NPCs apoptosis by promoting autophagic ux.…”
Section: Resultsmentioning
confidence: 95%
“…There were reports that exosomes could attenuate diabetic nephropathy and D-GaIN/LPS-induced hepatocyte injury by promoting autophagic ux and inhibiting apoptosis [31,32]. Therefore, we also examined whether exosomes could inhibit NPCs apoptosis by promoting autophagic ux.…”
Section: Resultsmentioning
confidence: 95%
“…In another hepatic injury study, the EVs from MSC exhibited protective effects on the hepatocytes despite being treated with liver injury stimulant drugs, partly via the upregulation of hepatocyte proliferation [74]. Other studies of EVs from the various origins of MSCs showed similar hepatic protective and regenerative effects, as seen in the bone-marrow-derived MSCs [75][76][77][78][79][80], human umbilical cord-derived MSCs [81][82][83], human liver stem cells [84,85], induced pluripotent stem cell-derived MSCs [86], human embryonic-derived MSCs [64], human menstrual blood-derived MSCs [87], and adipose-derived MSCs [88][89][90][91]. As for the prevention of fibrosis via the suppression of HSCs, a study of EVs from the chorionic plate-derived MSCs showed that these EVs suppressed the activation and proliferation of HSCs due to the presence of miR-125b in the cargo, thus preventing liver fibrosis [92].…”
Section: Evs From the Mesenchymal Stem Cells As A Treatment Optionmentioning
confidence: 82%
“…Thus, at least, these pathways mediated autophagy flux inside cells [109]. Surprisingly, exosomal miR-30a and miR-125b-5p which derived from transplanted MSCs represents the protective effect on I/R-induced injuries in cardiomyocytes by autophagy regulation through the Akt/AMPK/mTOR pathways both in vitro and in vivo studies [116][117][118]. It seems that activation of the PI3K/AKT/mTOR signaling pathway reduces excessive autophagy and rescues cells from death.…”
Section: Cross-regulation By Akt/mtor Signaling Pathwaymentioning
confidence: 99%
“…Liu et al found that exosomes from MSCs increased autophagy in cardiomyocytes through AMPK/mTOR pathway and reduced adverse effects of myocardial I/R injury [109]. Besides, MSCs-derived exosomes transfer miR-30a and miR-125b-5p, which participate in improving I/R-induced injuries in cardiomyocytes by modulating autophagy via the Akt/mTOR signaling pathways both in vitro and in vivo studies [116][117][118]. Therefore, MSCs derived exosomes have potential to modulate autophagy in cells of cardiovascular system, proposing clinical application in CVD treatment.…”
Section: Clinical Translation Potential Of Exosomes-mediated Autophagymentioning
confidence: 99%